A Gender- and Culturally Sensitive Weight Loss Intervention for Hispanic Men: Results From the Animo Pilot Randomized Controlled Trial. (October 2019) - Garcia, David O.; Valdez, Luis A.; Aceves, Benjamin; Bell, Melanie L.; Humphrey, Kyle; Hingle, Melanie; McEwen, Marylyn; Hooker, Steven P.
Background . Hispanic males have the highest rates of overweight and obesity compared with men of all other racial/ethnic groups. While weight loss can significantly reduce obesity-related health risks, there is limited research examining effective gender- and culturally tailored behavioral weight loss programs for Hispanic men. Objective . To assess the feasibility and preliminary efficacy of a 12-week gender- and culturally sensitive weight loss intervention (GCSWLI) as compared with a waist-list control (WLC) in sedentary, Hispanic males with overweight/obesity. Method . Fifty Hispanic males (age: 43 years [ SD = 11]; BMI: 34 ± 5 kg/m 2 ; 58% Spanish monolingual) were randomized to one of two groups: GCSWLI ( n = 25) or WLC ( n = 25). GCSWLI participants attended weekly in-person individual sessions with a bilingual, bicultural Hispanic male lifestyle coach, and were prescribed a daily reduced calorie goal and 225 minutes of moderate-intensity physical activity per week. The WLC were asked to maintain their usual diet and physical activity habits for 12 weeks. GCSWLI participants continued with 12 additional weeks of follow-up including biweekly phone calls with lifestyle coaches. Results . At Week 12, the mean weight loss in the GCSWLI was −6.3 kg (95% confidence interval [CI; −8.1, −4.4]) compared with −0.8 kg (95% CI [−2.5, 0.9]) for the WLC (difference = −5.5 kg, 95% CI [−8.0, −2.9], p < .01). At Week 24, weight loss in the GCSWLI was maintained. Conclusions . The GCSWLI appears to be a feasible strategy to engage Hispanic males in short-term weight loss. Our pilot study indicates preliminary evidence of efficacy, though confirmation of these findings is needed in a larger study.